Antibiotic Discontinuation 24 h After Neonatal Late-Onset Sepsis Work-Up—A Validated Decision Tree Model - Goldberg, Ori; Sokolover, Nir; Bromiker, Ruben; Amitai, Nofar; Chodick, Gabriel; Scheuerman, Oded; Ben-Zvi, Haim; Klinger, Gil (Frontiers in Pediatrics, 2021)
Objectives: Neonatal late-onset sepsis work-up is a frequent occurrence in every neonatal department. Blood cultures are the diagnostic gold standard, however, a negative culture prior to 48-72 hours is often considered insufficient to exclude sepsis. We aimed to develop a decision tree which would enable exclusion of late-onset sepsis within 24 hours using clinical and laboratory variables. Study design: Infants evaluated for late-onset sepsis during the years 2016-2019, without major malformations, in a tertiary neonatal center were eligible for inclusion. Blood cultures and clinical and laboratory data were extracted at 0 and 24 hours after sepsis work-up. Infants with bacteriologically confirmed late-onset sepsis were compared to matched control infants. Univariate logistic regression identified potential risk factors. A decision tree based on Chi-square automatic interaction detection methodology was developed and validated. Results: The study cohort was divided to a development cohort (105 patient) and a validation cohort (60 patient). At 24 hours after initial evaluation, the best variables to identify sepsis were C-reactive protein > 0.75 mg/dl, neutrophil-to-lymphocyte ratio > 1.5 and sick-appearance at 24 hours. Use of these 3 variables together with blood culture status at 24 hours, enabled identification of all infants that eventually developed sepsis through the decision tree model. Our decision tree has an area under the receiver operating characteristic curve of 0.94 (95% CI:0.90-0.98). Conclusions: In non-sick appearing infants with a negative blood culture at 24 hours and normal laboratory values, sepsis is highly unlikely and discontinuing antibiotics after 24 hours is a viable option.